The big push : exposing and challenging the persistence of patriarchy - Enloe, Cynthia H., 1938- (University of California Press, 2017)
"For over a century and in scores of countries, patriarchal presumptions and practices have been challenged by women and their male allies. "Sexual harassment" has entered common parlance; police departments are equipped with rape kits; more than half of the national legislators in Bolivia and Rwanda are women; and a woman candidate won the plurality of the popular votes in the 2016 United States presidential election. But have we really reached equality and overthrown a patriarchal point of view? The Big Push exposes how patriarchal ideas and relationships continue to be modernized to this day. Through contemporary cases and reports, renowned political scientist Cynthia Enloe exposes the workings of everyday patriarchy--in how Syrian women civil society activists have been excluded from international peace negotiations; how sexual harassment became institutionally accepted within major news organizations; or in how the UN Secretary General's post has remained a masculine domain. Enloe then lays out strategies and skills for challenging patriarchal attitudes and operations. Encouraging self-reflection, she guides us in the discomforting curiosity of reviewing our own personal complicity in sustaining patriarchy in order to withdraw our own support for it. Timely and globally conscious, The Big Push is a call for feminist self-reflection and strategic action with a belief that exposure complements resistance."--Provided by publisher
Keywords: Patriarchy.; Sex role.; Feminism -- Social conditions.; Patriarchy -- History.; Sexual harassment.; Women -- Economic conditions.; Patriarchy -- Social aspects -- Syria.; Sexual harassment of men.; Sexual harassment of women.; Patriarcat (Sociologie); Rôle selon le sexe.; Féminisme -- Conditions sociales.; Patriarcat (Sociologie) -- Histoire.; Harcèlement sexuel.; Femmes -- Conditions économiques.; Patriarcat (Sociologie) -- Aspect social -- Syrie.; sex role.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; SOCIAL SCIENCE -- Feminism & Feminist Theory.; Sexual harassment of women; Sexual harassment of men; Patriarchy; Sex role; Sexual harassment; Women -- Economic conditions; Syria; gender womens studies.; lesbian rights.; lgbt rights.; male allies.; patriarchal society.; patriarchy.; presidential election.; rape kits.; secretary general of the un.; self reflection.; sexual harassment.; womens rights advocate.; womens rights.; History